Kleinskalige Charakterisierung der Fest-Flüssig-Trennung und Betrachtung des Scherbruchs von Proteinkristallen - Radel, Benjamin (KIT Scientific Publishing, 2022)
Proteins are macromolecules composed of amino acids that are essential for a large number of biological metabolic processes. Proteins are also used in technical applications, for example to catalyze reactions. The objective of this work is to provide an indication of filterability early in the process development. A filtration cell for a centrifuge developed in this work makes it possible to characterize filtration on a small scale.